Thermodynamic analysis of CO2 blends for vehicle heat pump at cold ambient temperature - Li, Chengyu; Liu, Zhaoqiang; Sun, Binbin; Wang, Youtang; Gao, Song; Zhang, Tiantian; Wang, Baolong (Frontiers in Energy Research, 2022)
Heat pump is promising way of energy conservation to improve driving range of electric vehicles. In this study, thermodynamic characteristics of CO2–based blends in operation of a subcritical heat pump cycle are evaluated under different ambient temperature, considering two operation modes. Coefficient of performance (COP) and volumetric heating capacity (VHC) are used to evaluate heat pump performance. Optimization and comparison of both transcritical and subcritical cycle are conducted using various refrigerants. The results indicate that CO2/R32 (50/50) always outputs higher COP than CO2 or other mixtures. The COP of CO2/R41 (90/10) is inferior to CO2 in a transcritical cycle due to larger compression work consumption. The blends of R1234yf and R152a with low-GWP have lower COP, but much lower operation pressure is also achieved. CO2 blends have larger volumetric heating capacity, which will facilitate simple cycle configuration and compact compressor.